An index for assessing the rare species of a community - Everton A. Maciel (Elsevier, 2021)
Rarity has long been a question of great interest in a wide range of fields. A method to classify rare species should be simple and easy for different professional groups to learn. Rabinowitz is not only easy-to-follow but also one of the most accepted methods to classify rare species. This study proposes a rarity index (rr) based on Rabinowitz’s scheme. The index operates at the species level. Given a list of n species, the inverse of the geographical range in decimal degree (geographic range index – gri) of the maximum number of species habitats (habitat specificity index – hsi), and the maximum population size anywhere (population size index – psi) were calculated for each species. An average index rr = med(gri + hsi + psi) was calculated for each species from the gri, hsi, and psi indexes. The rr varies from 0 to 1: the closer rr is to 1, the rarer the species. A code in the R language to calculate each proposed measure is provided. The output of this code is a list of species with their respective indices. RR is useful in the ecology and biodiversity conservation fields. This index has the following advantages: (1) it uses three aspects of rarity to gain a synthetic index; (2) the three parameters have equal weights; and (3) it is easily followed by anyone who feels inclined to use it. Some directions on how it might be used are discussed.